2007
DOI: 10.1037/0012-1649.43.1.238
|View full text |Cite
|
Sign up to set email alerts
|

The development of infant discrimination of affect in multimodal and unimodal stimulation: The role of intersensory redundancy.

Abstract: This research examined the developmental course of infants' ability to perceive affect in bimodal (audiovisual) and unimodal (auditory and visual) displays of a woman speaking. According to the intersensory redundancy hypothesis (L. E. Bahrick, R. Lickliter, & R. , detection of amodal properties is facilitated in multimodal stimulation and attenuated in unimodal stimulation. Later in development, however, attention becomes more flexible, and amodal properties can be perceived in both multimodal and unimodal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
265
2
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 302 publications
(286 citation statements)
references
References 77 publications
11
265
2
8
Order By: Relevance
“…For example, the greater amount of information provided through multisensory stimulation could increase infants' general arousal and provide them with more information through which to compare numerical values. To discount this hypothesis, prior studies asking whether intersensory redundancy enhances cognitive, perceptual, and even social development have run control conditions in which asynchronous or non-redundant multisensory information is presented to the infant (i.e., Bahrick and Lickliter, 2000;Flom and Bahrick, 2007;Lickliter et al, 2002Lickliter et al, , 2004. In all such situations, infants fail to discriminate the property being tested unless it is synchronously and redundantly specified across multiple modalities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the greater amount of information provided through multisensory stimulation could increase infants' general arousal and provide them with more information through which to compare numerical values. To discount this hypothesis, prior studies asking whether intersensory redundancy enhances cognitive, perceptual, and even social development have run control conditions in which asynchronous or non-redundant multisensory information is presented to the infant (i.e., Bahrick and Lickliter, 2000;Flom and Bahrick, 2007;Lickliter et al, 2002Lickliter et al, , 2004. In all such situations, infants fail to discriminate the property being tested unless it is synchronously and redundantly specified across multiple modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous developmental studies of emotion recognition reported that emotion recognition is initially promoted in naturalistic, multimodal conditions and that this ability is later extended to auditory and visual unimodal conditions [28,29]. For example, a study by Flom et al [29] revealed that fourmonth-old infants discriminate happy, sad and angry emotions through audiovisual bimodal stimulations, but that sensitivity to auditory stimuli emerges at five months and that to visual stimuli emerges at seven months.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Flom et al [29] revealed that fourmonth-old infants discriminate happy, sad and angry emotions through audiovisual bimodal stimulations, but that sensitivity to auditory stimuli emerges at five months and that to visual stimuli emerges at seven months. This notion is also supported by event-related potential studies [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations